Minor and field-names of Thurgarton Wapentake, Nottinghamshire - Gregory, Rebecca Katharine (2017)
This thesis investigates the minor and field-names of twenty-two parishes in Thurgarton Wapentake, a historic division of Nottinghamshire. It investigates the agricultural history of the region, and explores the usage of Old English and Old Norse-derived place-name elements in the late medieval period.